PERCERAIAN PEGAWAI NEGERI SIPIL TANPA DISERTAI IZIN PEJABAT YANG BERWENANG DAN AKIBAT HUKUMNYA - Indra Budi Prasetya (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT That the factors causing the absence of official permission in the civil servant divorce case in the Religious Court of Samarinda are: the civil servant concerned does not take the procedure of granting licenses in BKPPD of Samarinda City Government; Difficult procedure of divorce permit In BKPPD Government of Samarinda City; The discontinuation of the procedure for granting a divorce permit in BKPPD of Samarinda City Government; Officials do not issue a Decision Letter in accordance with the specified time period. Based on the provisions of Article 49 of Law Number Year 2006 one of the jurisdictions of religious courts is to examine, decide and settle matters in the field of marriage in the first level between people who are Muslims. Understanding the field of marriage here are all things that are regulated in the UUP, including among others on the case of divorce. In the handling of divorce cases, religious courts are authorized to handle divorce cases at the first level among Muslims, including divorce from civil servants who are Muslims. In relation to the divorce of civil servants, in addition to heeding the general provisions contained in the UUP and Government Regulation No. 9 of 1975, religious courts must also heed the special provisions contained in Government Regulation No. 45 of 1990 on Amendment to Government Regulation No. 10 of 1983 on Marriage and Divorce of civil servants. The legislation as mentioned above, is a material law that is used as a guide by religious courts in solving the case of divorce. Although the UUP and Government Regulation No. 9 of 1975 and Law No. 3 of 2006 contain the rules of material law in settling divorce cases, but basically the things that are set in it are just the point. The rule has not yet elaborated on the overall provisions of marriage law regulated in Islam.